The effect of pomalidumide on inflammatory factors and Antioxidant-Prooxidant balance in Rat Model of Ovalbumin-induced Asthma - Majid Ghaderi Dr; Shahrbanoo Oryan; Namdar Yousofvand; Akram Eidi (مجله علمی دانشگاه علوم پزشکی کردستان, 2019)
Background and Aim: Allergic asthma is an inflammatory disease of the respiratory system which causes an increase in inflammatory factors such as IL-2,IL-4,IL-5, lymphocytes and eosinophils. These factors can increase the level of free radicals and oxidants. Pomalidumide, an anti-inflammatory drug that has stronger effects than its analogues, can significantly reduce inflammatory factors. The aim of this study was to evaluate the effect of pomalidumide on inflammatory factors and pro-oxidant antioxidant balance in the rat model of ovalbumin-induced asthma. Material and Methods: Male rats were divided into 5 groups (n=8): normal saline, ovalbumin+normal saline, ovalbumin+dexamethasone, ovalbumin+pomalidimide (0.4 0.8 mg/kg, ip). We used ELISA method to determine the level of inflammatory factors. We measured pro-oxidant-antioxidant balance (PAB) for assessment of blood oxidant level. Results: We found significant decrease in the levels of inflammatory factors in the pomalidumide group. This decrease was more significant in the group that received pomalidumide 0.8 mg/kg, ip. Conclusion: The results of this study showed that pomalidomide prevented the pro-oxidant antioxidant balance shift towards increasing oxidant factors in the asthmatic rats. Also it prevented increase in inflammatory factors including IL-2, IL-4,IL-5, lymphocytes and eosinophils in the ovalbumin-induced asthma rat model.